Wartość przepływów pieniężnych w ubezpieczeniach życiowych - Marciniuk, Agnieszka (Value of Life Insurance Cash Flows, 2007)
The traditional calculations of actuarial values are made under the assumption that the interest rate is fixed and constant for all years. However, the market interest rates are varying in time, so in the modern actuarial theory premiums and reserves are calculated with regard to these changes. First the cash flows are defined. Then the values of cash flows are discounted in a particular moment of time by the use of the instantaneous interest rate. Then their values are calculated according to the principles of financial markets. This procedure is presented in the paper. This valuation relies on finding such an equivalent measure that the discounted process of value of cash flow will be a martingale. Such a measure is called an equivalent martingale measure. In the article some life insurance cash flows are presented. Then valuation of these cash flows is performed. All the calculations are illustrated by examples.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 188-207